Evaluation of stress response in middle-aged male diabetic hypertensive patients - KAŞKAL, MERT (My University, 2023)
Context Stress triggers a cascade of reactions that alter the organism\"s dynamic steady state. There is a scarcity of interventional studies that show cortisol variability upon stress over time in groups of patients with chronic noncommunicable diseases and comorbidities. Objective We aimed to examine salivary cortisol changes in the cognitive stress response of patients with hypertension and diabetes mellitus (HT&DM) and patients with hypertension (HT) and to determine differences between them. Methods The study was conducted using a stress test of solving an arithmetic task in 62 patients with HT&DM and HT who were being treated in the outpatient clinic of the Medical Pharmacology and Clinical Pharmacology Department in Istanbul University, Istanbul Medical Faculty Hospital. Results There was no statistically significant difference between the HT&DM and HT groups for systolic blood pressure (SBP) and diastolic blood pressure (DBP) values (P = .331 and P = .058). When measured by repeated ANOVA, salivary cortisol level [F (1.842, 60) = 8.771, P < .0001], SBP [F (2.185, 60) = 12.080, P < .0001], DBP [F (2.793, 60) = 6.043, P = .001], and heart rate [F (2.073, 60) = 13.259, P < .0001] were statistically significant for the main effect (time), while the effect of the group x time interaction factor was statistically not significant (P = .773; P = .751; P = .713 and P = .506, respectively). Conclusion The arithmetic problem-solving task used with the HT&DM and HT patients was useful as an acute stress test in the laboratory environment. There was no statistically significant difference for group x time interaction factor between the HT&DM and HT groups; however, the salivary cortisol and BP values increased significantly after acute stress within each group.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Endokrinoloji ve Metabolizma Hastalıkları; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Endocrinology and Metabolic Diseases; Health Sciences; ENDOKRİNOLOJİ VE METABOLİZMA; Klinik Tıp; Klinik Tıp (MED); ENDOCRINOLOGY & METABOLISM; CLINICAL MEDICINE; Clinical Medicine (MED); Endokrin ve Otonom Sistemler; Endokrinoloji, Diyabet ve Metabolizma; Endokrinoloji; Yaşam Bilimleri; Endocrine and Autonomic Systems; Endocrinology, Diabetes and Metabolism; Endocrinology; Life Sciences; hypertension; diabetes mellitus; stress test; salivary cortisol; CORTISOL RESPONSE; PSYCHOLOGICAL STRESS; SALIVARY CORTISOL; PLASMA-CORTISOL; MENTAL STRESS; REACTIVITY; GLUCOSE; WOMEN